Experimental Study of the Shear strength of Self Compacting Concrete T-Beams made with Recycled Concrete as Coarse Aggregate - Ali Kadr Khtar; Asst. Prof. Dr. Jamal Abdul Samad Khudhair (University of Thi-Qar Journal, 2019)
This paper presents the test results of an experimental study on shear strength of reinforced concrete T-beams cast using self- compacting concrete (SCC) with recycled concrete aggregate (RCA) as a partial replacement of coarse aggregate. Twenty seven T-beams were cast and tested, the variables were the shear span to effective depth ratio (1, 2 and 3) , the RCA replacement ratio (0% ,50% and 75%) and the amount of web reinforcement. The beams were tested under four-point load condition. During the test, the values of the first crack load and the ultimate load were observed as well as the deformation of the beams. The experimental results indicated that when increasing the RCA replacement ratio to 50%, the first cracking load and the ultimate load reduced by an average of 30% and 6% respectively. When the RCA replacement ratio was 75%, the first cracking load and the ultimate load reduced by 31.6% and 9.4% respectively. It can be observed that, at the load 500kN, T-beams with the higher replacement ratio of RCA exhibited slightly higher deflection. Also the first cracking load and the ultimate load decreased with the increase of (a/d) ratio. The presence of web reinforcement causes an increase of about 16% in cracking load. This increase seems to be independent of a/d ratio and the RCA replacement ratio. The average increase in ultimate loads were 4.4% , 18.9% and 28.4% for a/d ratio of 1, 2 and 3 respectively.The presence of web reinforcement slightly reduced the measured deflection and crack width, and its effect was more for the lower stirrup spacing.